Peran Kewbawaan Dan Kedisiplinan Guru Pendidikan Agama Islam Dalam Menumbuhkan Kemandirian Belajar Peserta Didik di SMK Negeri 1 Blora - Siti Nur Khabibah; Ahmad Saiful Rizal; Achmad Abdul Azis (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study was motivated by the important role of Islamic Religious Education teachers in fostering students’ independent learning in schools. Independent learning is an important aspect that students must possess in order to take responsibility for their own learning process. In this context, the authority and discipline of teachers are factors that can influence the development of students’ learning independence. This study aims to describe the role of the authority and discipline of Islamic Religious Education teachers in fostering students’ independent learning at SMK Negeri 1 Blora, to examine the development of students’ learning independence, and to identify the supporting and inhibiting factors in its implementation. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research subjects consisted of Islamic Religious Education teachers and several students at SMK Negeri 1 Blora. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results show that the authority and discipline of Islamic Religious Education teachers play an important role in fostering students’ independent learning. Teacher authority is reflected in firmness, exemplary behavior, and the ability to manage the classroom effectively. Meanwhile, teacher discipline is reflected in consistency in carrying out responsibilities, such as punctuality, preparation of learning materials, and consistent implementation of classroom rules. These attitudes positively influence the development of students’ independent learning, including increased responsibility in completing assignments, active participation in learning, and the ability to learn independently. Supporting factors include teacher role modeling, students’ learning motivation, and a conducive classroom environment. The inhibiting factors include differences in students’ characteristics and varying levels of self-confidence.